The trophic ecology of the endangered endemic Barau's Petrel (Pterodroma baraui) from Reunion Island, south-western Indian Ocean - Danckwerts, Daniel Keith (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Réunion is the only tropical island that supports two endemic gadfly petrels. Population modelling has indicated that the current threats to the Barau's Petrel (Pterodroma baraui) may drive it to extinction; this fate is almost definite for the Mascarene Petrel (Pseudobulweria aterrima). Management interventions have therefore been implemented, but conservation potential is handicapped since virtually nothing is known about the former species' at-sea biology. Thus, following numerous recommendations, this study aimed to combine stomach content, stable isotope, and fatty acid analyses so to provide new information on the at-sea ecology of Barau's Petrel. Breeding colonies were repeatedly visited over the same season and samples gathered from adults, fledglings, and downy chicks. Stomach contents consisted mostly of accumulated cephalopod beaks whereas structures from fishes, molluscs, arthropods, and crustaceans were less frequently encountered. Fatty acid profiles of blood varied greatly among individuals and the lowincidences of monounsaturated and n-3 fatty acids discounted fish as an important dietary component. Î´Â¹â µN of blood indicated a niche between the fourth and fifth trophic levels, which proposes that these birds scavenge to a greater degree than other sympatric seabirds and suggests that adults are also reliant on their endogenous reserves during breeding. Î´Â¹Â³C values confirmed the migratory behaviour of adults since birds returning from the non-breeding grounds were enriched relative to individuals sampled through the breeding period. Significant intra-breeding season variations in Î´13C were also observed, which matched this species' patterns of habitat use as have recently described. These results collectively indicate an opportunistic behaviour, which implies some degree of resilience against shifts in prey availability/accessibility, and suggest that this species' reproduction isdependent on distant foraging areas. This breeding strategy is synonymous with great vulnerability as over-investing into a single breeding episode may jeopardize future survival and fecundity. Thus, in light of environmental conditions that are becoming increasingly more susceptible to dramatic changes, the birds could rather be prioritising adult survival, over reproductive output. Further work is obviously necessary and should benefit from databases of fatty acid profiles and isotope signatures of potential prey species.
Keywords: Petrels -- Réunion; Pterodroma baraui; Ecology -- Réunion